2023
DOI: 10.1037/vio0000473
|View full text |Cite
|
Sign up to set email alerts
|

Sexual stigma, masculinity, and physical intimate partner violence perpetration among sexual minority men.

Abstract: Objective: The present study examined whether sexual minority men's experiences of sexual stigma and conformity to masculine norms predicted their perpetration of physical intimate partner violence (IPV) and whether masculinity norms and sexual orientation moderated those relationships. Method: Two hundred seventy-five gay and bisexual+ (bi+) men completed online questionnaires assessing their physical IPV perpetration in their most significant recent intimate relationship, along with measures of sexual stigma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…The association between IPV, dark personality traits, conformity to masculine norms and the role of sexual stigma could be explored. This represents a potential line of future research building on work by Harris and Mahalik (2023) into sexual stigma, masculinity and physical IPV among sexual minority men.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between IPV, dark personality traits, conformity to masculine norms and the role of sexual stigma could be explored. This represents a potential line of future research building on work by Harris and Mahalik (2023) into sexual stigma, masculinity and physical IPV among sexual minority men.…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence studies for this collective sexual minority group have estimated that between 34% and 45% of men in a same-sex relationship have been subjected to IPV (Maxwell et al, 2020). Other research has indicated that IPV victimisation rates may be as high as 26% for gay males as a sexual minority group and 27.3% for bisexual males (Harris & Mahalik, 2023). Furthermore, in comparison to heterosexual males, "sexual minority men were twice as likely to be victims of IPV and 1.7 times as likely to perpetrate IPV" (Harris & Mahalik, 2023, p. 297).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded participants who indicated that they are heterosexual ( n = 12), questioning ( n = 1), women ( n = 6), or did not answer the gender identity question on the survey ( n = 1). As this study’s data were collected as part of another study examining experiences of sexual minority men in relationships (Harris & Mahalik, 2023), participants who reported that they were not in a relationship in the last year ( n = 5) were also excluded. We also used the Mahalanobis procedure to identify any outliers ( n = 1).…”
Section: Methodsmentioning
confidence: 99%